Theological Study of the Role of the Holy Spirit as the Antithesis of Liberal Theology - Elisabeth Faomasi Gea; Yeremia Putra Danurja; Ekky Oktapian (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines liberal theology, which emerged in the early 20th century and is rooted in modern philosophy and rationalism, emphasizing the capacity of human reason as the source of truth. This understanding created a crisis of biblical authority because it rejected fundamental doctrines of the Christian faith and reduced Jesus to a mere moral teacher. As an antithesis, the Holy Spirit in biblical theology is understood as a personal God who guides believers to all truth. Through His work, the Holy Spirit reveals divine truth that transcends the limitations of human reason, affirms the authority of the Bible, and empowers people to live in true faith. The research method used is a literature review with a theological-systematic approach and descriptive-comparative analysis. The results show that only through the help of the Holy Spirit can the church resist the influence of liberal theology, maintain the purity of its teachings, and bear faithful witness to Christ amidst the changing times.